Geotechnical and Structural Engineering Congress 2016 2016
DOI: 10.1061/9780784479742.162
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Foundation Stiffness Identification

Abstract: There are great economic incentives motivating the reuse of existing foundations when deteriorated and damaged superstructures are replaced. The increasing reuse of existing bridge foundations warrants investigation into verifying foundation performance and condition of in service bridge foundations. A method is proposed which characterizes the load-response behavior of existing bridge foundations during daily vehicular loading without impeding traffic. It uses a limited number of substructure response measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Figure 11b, however, shows that the phase difference was 180 • at 54. 19 Hz. These results demonstrated that the outer part of the pier behaved in opposite directions; thus, indicating torsional behavior.…”
Section: Full-scale Pier Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 11b, however, shows that the phase difference was 180 • at 54. 19 Hz. These results demonstrated that the outer part of the pier behaved in opposite directions; thus, indicating torsional behavior.…”
Section: Full-scale Pier Test Resultsmentioning
confidence: 99%
“…In addition, many studies have been conducted to judge the state of the pier by its natural frequency. Sanayei and Maser [19] conducted research on the static measurement by using a vehicle load to estimate the ground stiffness of a bridge foundation. When a 200 kN truck passed each bridge that was built on a pile foundation and a footing, respectively, the stiffness ratio of the measured and theoretical values according to the foundation type were compared.…”
Section: Introductionmentioning
confidence: 99%